The Role of Social Capital and NGOs in Community Based Management of Openwater Inland Fisheries of Bangladesh - Alia Ahmad (Lund University, School of Economics and Management, Department of Economics, 2003)
The aim of the paper is two-fold. It presents an integrated conceptual framework based on the literature on common-pool resource institutions, social capital and NGOs, and secondly, it applies the framework to the case of Bangladesh fisheries sector. Current theoretical and empirical research on common-pool resources arrive at two major conclusions: first, the tragedy of the commons is not an inevitable outcome, and secondly, sustainable management of CPRs depends not only on bio-physical characteristics and user characteristics but also on a broader institutional framework or social capital. Formal institutions and externally-supported NGOs can play an important role in this context. The experience of Bangladesh openwater inland fisheries confirms that private property rights attached to waterbodies largely solve the problem of appropriation externalities, but have failed to fulfill equity and long-term sustainability goals because of the elite capture of fishing rights. Community-based fisheries management supported by NGOs since the early 1990s has addressed these problems with some success. Two factors appear to determine their performance: the support of formal institutions (legal, administrative), and the project design based on active participation of members that presupposes some social capital.
Keywords: O13; Q22; 330; Common-pool resources; NGOs; CBOs; social capital